Differentiation of Bone Marrow Stem Cells in Presence of Human and Xenogeneic Acellular Dermal Matrix and Collagen Membrane: an in vitro Study - Sepideh Gholamhoseinnia; Vahid Esfahanian; Shirin Amini Sedeh (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Predictable bone regeneration is an objective in implant and periodontal treatments and barrier membranes may play a significant role in osteogenic reconstruction and differentiation. Purpose: We compared the osteoblastic differentiation level of bone marrow stem cells in the vicinity of different barrier membranes. Materials and Method: In this experimental in vitro study, human collagen membrane (HCM; Regen), xenogeneic collagen membrane (XCM; Jason), human acellular dermal matrix (HADM; Regen), and xenogeneic acellular dermal matrix (XADM) were used in 4 groups. No membranes were used in the control group (5th group). Bone marrow stem cells with 150,000 cells/well density were added to the culture medium. Cellular differentiation was assessed through real-time quantitative reverse transcription polymerase chain reaction (QRT-PCR) for alkaline phosphatase (ALP) and osteopontin (OPN) gene expression, and Alizarin Red staining after 21 days. Data were analyzed using Kruskal- Wallis and Mann-Whitney statistical tests on SPSS 20 software (p Value< 0.05). Results: ALP gene expression was significantly higher in HCM group compared to other four groups (p< 0.009) followed by XADM, control, HADM and XCM groups, respectively (p< 0.001). OPN gene expression was significantly more prominent in HCM group compared to other groups (p< 0.01) followed by XADM group in which OPN gene was expressed significantly more than XCM group. OPN gene expression was not significantly different in HADM and control groups (p= 0.52). Light absorption rate was higher in HCM group compared with other groups (p< 0.012). Light absorption rate was not significantly different among HADM, XADM, and control groups (p> 0.05), though it was higher in XCM group (p= 0.009). Conclusion: Bone marrow stem cells show different levels of differentiation in the vicinity of different membranes. Generally, cell differentiation was more prominent in the vicinity of human collagen membrane.